Chapter Bullismo etnico pregiudiziale a scuola: il ruolo dei fattori strutturali e dei meccanismi psicologici - Basilici, Maria Chiara (Studies on Adult Learning and Education, 2022)
The increase in migration movement worldwide, and the consequent growth of multi-ethnic classes in schools have impacted on the implementation of ethnic bullying, a subtype of bias-based bullying in which victims are targeted because of their ethnic background. Despite the serious consequences of this discriminatory behaviour on the actors involved, research on the role of ethnicity in bullying is still limited. Upon these considerations, the present work aims to shed light on the role of structural factors and psychological mechanisms, explaining ethnic bullying in schools among natives and students with immigrant backgrounds. Specifically, this study is composed of three distinct parts: 1) a systematic review of the association between school and classes' ethnic diversity and bullying and victimization; 2) a cross-sectional study on the role of ethnic diversity (legal and perceived) on bullying victimization; 3) a longitudinal study on the differential impact of COVID-19 on victimization and emotional symptoms, focusing on natives and students with immigrant background. Finally, the main results of the three studies are discussed, the implications for future studies and interventions are suggested and, policy and education practices are recommended.